Light Manifesto: Non-Philosophy and Meteophilosophy - Sazonov, Nikita (Stasis, 2019)
Deleuze’s speculative suggestion on the dark precursor is not a neutral “creative” cooperation with science that his “hybrid” projects of geophilosophy, schizoanalysis, and so on, were. The dark precursor is mentioned once in Difference and Repetition as a notion of a “vaguely scientific” discipline, and there was no broad or explicit conceptual extension of it in Deleuze’s further philosophy. But at the same time, this accidental usage of the dark precursor uncovers the deep and fundamental sutures of recent speculative philosophy with the physical investigation of lightning. The fundamental questioning of philosophy, such as Quentin Meillassoux’s speculative movement on “hyperchaos,” is localized within the meteorological chains of the cosmic order of the principles of lightning’s genesis. In such meteophilosophy,we can find a way to suspend the transcendental limits of logocentrism, in its logo-photo-centric edition proposed by François Laruelle. Logo-photo-centric thought constituted by the light manifesto, or by the light as Flash, can be suspended by the anti-manifestational short-circuitsof meteophilosophy’s speculative models. Such short-circuits, from the other side, constitute the core of the lightmaresof thought that did not even come to Laruelle in his non-philosophical dreams.